Legal Implications in The Execution of a Will Without Making a Will Authentic Deed in the Conception of Legal Certainty - Nuha, Revana Mahran; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. The legal system in Indonesia is pluralistic in nature, in which it applies as a legal system that has its own characteristics and structure, namely the customary legal system, the Islamic legal system, the western legal system (civil). In this case, inheritance law is also regulated in it. Where in Islam, a